Helical structures of the cyanide degrading enzymes from Gloeocercospora sorghi and Bacillus pumilus providing insights into nitrilase quaternary interactions - Scheffer, Margot Petra (Department of Molecular and Cell Biology, 2014)
Includes bibliographical references.